Consolidating Rural Woman Power Key to Social Development. - Chandran , N.S. (Journal of Social Work Education and Practice, 2023)
The unexplored and unexploited power of rural women deeply ensnared in unproductive rustic life still remains disregarded in our country. We have sufficient funds and a large number of welfare programmes. Why then there is no expected outcome? The article focuses on the necessity of devising a professional mechanism so that the gains of all empowerment projects reach out to beneficiaries entirely. A persuasive partnership between Community Development Agencies and Government Departments is also imperative to unearth the hidden potentialities of rural women, mobilize their efforts and synergize or rather network their entrepreneurial abilities for self-sustenance and social development. A psychological approach, hitherto ignored should be looked into. The goal is to generate inquisitiveness and quest for freedom, the driving force which emancipates women from fear, insecurity and difficult life situations.
Keywords: Professional mechanism; Empowerment, synergize; Entrepreneurial abilities; Self- sustenance